A contribution to professionalism: reflecting on highly complex contexts in connection with a person-centered approach to counseling in social work. (2nd January 2023) - Mazurkiewicz, Lena
ABSTRACT: The field of social work is characterized by complex contexts. Against the backdrop of societal demands, institutional mandates, clients' needs and concerns, and the ethical principles of the profession, professionals must orient themselves in every situation. The article deals with the question of how the person-centered approach can contribute to an appreciative approach to clients in this context. In this theoretical elaboration, the Capabilities Approach as well as the recognition theory according to Honneth are also taken into consideration in order to establish the basis for a capability-oriented and humanistic professional attitude.